The Economics of "Big Five" European Football Leagues - Teodor Dima (CES Working Papers, 2015)
European football is a business with more and more attractive numbers for investors, shareholders or partners all over the planet. It has significantly changed especially over the last 20 years, following an intense procedure of acquisitions and marketing, a process that has brought important sums of money in this industry. This paper presents the overview of the “big five” European football leagues (England, Germany, Spain, Italy, France). The study is primarily focused on economics, but is also considering various social or cultural aspects (media, social media followers). The case-study on the five major leagues corroborates the theoretical underpinning. The paper investigates also the roots of financial regulation divergence in Europe and underlines the main issues regarding the UEFA financial fair-play rules.
Keywords: L83; M21; J31; 330; economic outlook; football leagues; financial fair play; social media